2017
DOI: 10.1016/j.celrep.2017.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Neto Auxiliary Subunits Regulate Interneuron Somatodendritic and Presynaptic Kainate Receptors to Control Network Inhibition

Abstract: Although Netos are considered auxiliary subunits critical for kainate receptor (KAR) function, direct evidence for their regulation of native KARs is limited. As Neto KAR regulation is GluK subunit/Neto isoform specific, such regulation must be determined in cell-type specific contexts. We demonstrate Neto1/2 expression in somatostatin- (SOM), cholecystokinin/cannabinoid receptor 1- (CCK/CB1), and parvalbumin- (PV) containing interneurons. KAR-mediated excitation of these interneurons is contingent upon Neto1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 63 publications
(135 reference statements)
4
46
0
Order By: Relevance
“…To better understand the mechanisms related to the behavioral phenotype of the Neto2 -/mice, we investigated Neto2 expression pattern that remains poorly characterized. Previous studies have shown that it is highly expressed in the cerebellum [3,5], and that in the Hpc it co-localizes with major KAR subunits in interneurons [8]. To determine the expression pattern of Neto2 in fear-related brain regions [i.e.…”
Section: Neto2 Is Expressed In Both Excitatory and Inhibitory Cells Imentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the mechanisms related to the behavioral phenotype of the Neto2 -/mice, we investigated Neto2 expression pattern that remains poorly characterized. Previous studies have shown that it is highly expressed in the cerebellum [3,5], and that in the Hpc it co-localizes with major KAR subunits in interneurons [8]. To determine the expression pattern of Neto2 in fear-related brain regions [i.e.…”
Section: Neto2 Is Expressed In Both Excitatory and Inhibitory Cells Imentioning
confidence: 99%
“…NETO2 expression is highest in the cerebellum where it plays a crucial role in determining KAR subunit composition at the postsynaptic density [5]. The expression of NETO1 is highest in the hippocampus (Hpc) [3], where it regulates KAR-mediated excitatory post-synaptic currents [4,8] and axonal targeting of KARs [9]. Recently Wyeth et al [8] showed that both NETO1 and NETO2 tonically inhibit cholecystokinin (CCK)-expressing interneurons and that NETO1 regulates KAR-mediated excitation of interneurons in the developing Hpc.…”
Section: Introductionmentioning
confidence: 99%
“…We have generated several isoform specific antibodies but they could only detect Neto-α when overexpressed (not shown). Similar challenges have been encountered in the vertebrate Neto field (Wyeth et al, 2017).…”
Section: Discussionmentioning
confidence: 63%
“…Other CUB/Sushi-containing proteins have been described in previous reports as auxiliary subunits of synaptic ionotropic glutamate receptors that regulate receptor subunit composition, localization, clustering, and transport throughout the dendritic arbor and finally to the synapse (Gendrel et al, 2009;Ng et al, 2009;Cousins et al, 2013;Fisher and Mott, 2013;Lomash et al, 2017;Wyeth et al, 2017). Additionally, Reelin has been reported to induce signal transduction through phosphoinositide-3 kinase (PI3K) to enhance surface insertion of AMPA receptors (AMPARs), contributing to an enhanced NMDAR response (Qiu et al, 2006).…”
Section: Discussionmentioning
confidence: 98%